Negroes Washing Clothes, Barbados - W. L. Johnson & Co., Ltd., Barbados. No. 66 (The Main Library, University of the West Indies, Cave Hill Campus, Barbados is responsible for making this digital resource available., 2023)
This is a scene of negro women washing clothes along the river side. There are trees on both sides of the river. A cow is seen grazing along one side of the river bank, while a boat has been pulled up on the other side. This is a divided back postcard. Back of the Postcard W.L. Johnson and Company Limited, Barbados N0.66 03 A MN & P £6 249232 (Handwritten in Pencil)
Landscape, Colour, “3 ½” x 5½ ”
Keywords: Rivers; Boats; Cows; Laundry; Clothes washing